Experience and Knowledge of Pain Management in Patients Receiving Outpatient Cancer Treatment: What Do Older Adults Really Know about Their Cancer Pain?. Issue 1 (4th October 2013) - Baker, Tamara A.; O'Connor, Melissa L.; Krok, Jessica L.
Abstract Objective An individual's ability to effectively manage their cancer pain is influenced by knowledge and perceptions regarding the pain experience. While significance of the physician's knowledge of cancer pain management has been reported, much less is known how a patient's knowledge may influence their ability to optimally manage their pain. The purpose of this study is to determine the influence health and social factors have on the knowledge and experience of cancer pain among older adults. Design A prospective cross‐sectional study of older Black and White patients presenting for outpatient cancer treatment. Methods Participants were surveyed on questions assessing pain severity, knowledge and experience of pain, self‐efficacy for pain treatment, satisfaction with pain treatment, and additional social, health, and demographic characteristics. A series of hierarchical regression models were specified to examine predictors of cancer pain knowledge and experience. Results Education, race, and trust were significant predictors of pain knowledge, whereas self‐efficacy for pain, pain interference, and pain severity were indicators of the experience of cancer pain. Conclusions Knowledge and experience of (cancer) pain are contingent upon a myriad of social and clinical factors that are not exclusive but rather coexisting determinants of health. Understanding older adults' knowledge of pain may begin to diminish the imparities in the diagnosis and treatment of pain among this growing diverse population of older adults. It may similarly allow for programs to be tailored to fit the specific needs of the patient in the treatment and management of their cancer pain.